Pediatric reference data for lean tissue properties: density and hydration from age 5 to 20 y - Wells, Jonathan CK; Williams, Jane E; Chomtho, Sirinuch; Darch, Tegan; Grijalva-Eternod, Carlos; Kennedy, Kathy; Haroun, Dalia; Wilson, Catherine; Cole, Tim J; Fewtrell, Mary S (The American journal of clinical nutrition, 2010)
BACKGROUND: Hydrometry and densitometry are widely used to assess pediatric body composition due to their ease of application. The accuracy of these techniques depends on the validity of age- and sex-specific constant values for lean tissue hydration or density. Empirical data on these constants, and their variability between individuals, are lacking. OBJECTIVES: The objectives were to measure lean tissue hydration and density in a large sample of children and adolescents and to derive prediction equations. DESIGN: Body composition was measured in 533 healthy individuals (91% white) aged 4-23 y by using the 4-component model. Age- and sex-specific median values for hydration and density were obtained by using the LMS (lambda, mu, sigma) method. Regression analysis was used to generate prediction equations on the basis of age, sex, and body mass index SD score (BMI SDS). Values were compared with those in previously published predictions. RESULTS: Age-associated changes in density and hydration differed between the sexes. Compared with our empirical values, use of published values resulted in a mean bias of 2.1% fat (P < 0.0001). Age, sex, and BMI SDS were all significant predictors of lean tissue hydration and density. With adjustment for age and sex, hydration was higher, and density lower, in higher-BMI SDS individuals. CONCLUSIONS: The chemical maturation of lean tissue is not a linear process and proceeds differently in males and females. Previously published reference values are inaccurate and induce clinically significant bias in percentage fat. New empirical reference values are provided for use in pediatric hydrometry and densitometry. Further research that extends to cover nonwhite ethnic groups is needed.